Ginkgo Extract EGb761 Confers Neuroprotection by Reduction of Glutamate Release in Ischemic Brain - Alexander Mdzinarishvili; Rachita K. Sambria; Dorothee Lang; Jochen Klein (Frontiers Media S.A., 2012)
Purpose - Ginkgo extract EGb761 has shown anti-edema and anti-ischemic effects in various experimental models. In the present study, we demonstrate neuroprotective effects of EGb761 in experimental stroke while monitoring brain metabolism by microdialysis. Methods - We have used oxygen-glucose deprivation in brain slices in vitro and middle cerebral artery occlusion (MCAO) in vivo to induce ischemia in mouse brain. We used microdialysis in mouse striatum to monitor extracellular concentrations of glucose and glutamate. Results - In vitro, EGb761 reduced ischemia-induced cell swelling in hippocampal slices by 60%. In vivo, administration of EGb761 (300 mg/kg) reduced cell degeneration and edema formation after MCAO by 35-50%. Immediately following MCAO, striatal glucose levels dropped to 25% of controls, and this reduction was not significantly affected by EGb761. Striatal glutamate levels, in contrast, increased 15-fold after MCAO; after pretreatment with EGb761, glutamate levels only increased by 4-5fold. Conclusions - We show that pretreatment with EGb761 strongly reduces cellular edema formation and neurodegeneration under conditions of ischemia. The mechanism of action seems to be related to a reduction of excitotoxicity, because ischemia-induced release of glutamate was strongly suppressed. Ginkgo extracts such as EGb761 may be valuable to prevent ischemia-induced damage in stroke-prone patients. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.